부산광역시 농업·농촌 및 식품산업 발전 종합대책 - 박문호 (한국농촌경제연구원, 2009)
Recently, local agriculture and agricultural areas are confronted with a critical situation due to the rapid change of national and international conditions in agriculture and rural areas. Busan metropolitan city has invested in agriculture and rural areas based on several development measures for farming and fishing villages and 'agriculture and forestry investment and loan plan of government'. However, the establishment of systematic measures based on medium and long-term vision has not been sufficient so far. The purpose of this research is to establish the synthesised development plan of food industry as well as agriculture and rural areas by specifically examining local, environmental, and social-economic characteristics of rural areas, and evaluating the merits and demerits of local agriculture as well as its potential. Entire areas of Busan metropolitan city were set as the scope of the research, and plan period was divided into short-term and medium-long term by setting 10 years from 2010 to 2019. The current condition of agriculture and rural areas of Busan metropolitan city is identified according to sectors; agriculture production, distribution of agricultural products, food industry and rural development. The tasks of agriculture production are as follows: First, issue for the security of substitute farming land according to city development, second, issue of agricultural water, and third, issue of improving agriculture production facilities. The tasks of the distribution of agricultural products are as follows: First, the expansion of the direct distribution basis of agricultural products in accordance with the characteristics of the suburbs of the city is needed because agriculture environment depends on individual shipment due to the insufficiency of the appropriate sized organization of agricultural product local distribution. Second, the security of more distribution facilities is an important task where semi-process of agricultural products such as mini-packaging or rinsing can be conducted in the vicinity of consumption place. Third, the distribution measures to provide urban people with fresh and safe agricultural products is the important task as well. In terms of the task of food industry, on the account that Busan metropolitan city has the large-scale consumption market and holds superior logistics basis such as new harbor and Kimhae airport, intensive cultivation of food industry is required for the promotion of food import. In terms of the task of rural development, the role of urban and rural exchange and the offering of the resort and experience space for urban citizens are required for co-prosperity. The establishment of "Busan agricultural administration" as a field of the opinion collection is needed for the development direction of local agricultural adminstration and helping the understanding of local farmers about agricultural administration. In addition, the reinforcement of face to face consulting support for overcoming the problems of farming technology as well as item oriented specialized education is required.